Green synthesis and antibacterial potential of Artemisia vulgaris extract in silver nanoparticles against wound bacteria - Laura Soon; Phui Qi Ng; Jestin Chellian; Thiagarajan Madheswaran; Jithendra Panneerselvam; Alan Hsu; Philip Michael Hansbro; Kamal Dua; Trudi Collet; Dinesh Kumar Chellappan (Universitas Islam Indonesia, 2020)
Abstract Background: Artemisia vulgaris (A. vulgaris), a well-known Chinese traditional herb, is a potential agent for wound healing. The herb is reported for its antibacterial properties and is commonly used to control bleeding in women. In our project, we have developed A. vulgaris in silver nanoparticles to enhance its effect. Silver is already used in marketed wound bandages for its antibacterial effect. Understanding that it has a huge potential to be a safe and effective treatment for wounds, this study investigated the antibacterial effects of the synthesised AgNP on common wound bacteria.Objective: The objectives of this study are to synthesise A. vulgaris in silver nanoparticles and investigate the anti-bacterial effect of on wound bacteria. Method: The AgNP was synthesised by green synthesis method, which is done by mixing the silver nitrate solution with different concentrations of A. vulgaris extracts. The disc diffusion test, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests were carried out to investigate the antibacterial effects of the AgNP on common wound bacteria including K. pneumonia, P. aeruginosa, E. coli, B. cereus, S. aureus, and two strains of MRSA. The AgNP was also tested on probiotics using the disc diffusion test to investigate its effect on the probiotics.Results: The AgNP containing all plant concentrations were able to inhibit the growth of gram negative and gram positive bacteria. However, it required a higher concentration to inhibit the gram positive bacteria. The plant extracts and silver nanoparticles enhance each other’s effect to inhibit the growth of bacteria. Nanoparticles containing the A. vulgaris extracts have less inhibitory effects on probiotics compared to antibiotics and silver nitrate alone. However, statistical analysis showed that the antibacterial effect of the treatment was not statistically significant.Conclusion: The AgNP demonstrated anti-bacterial effects on both gram positive and gram negative wound bacteria, but the effect of the treatment is not statistically significant.Keywords: Artemisia vulgaris, silver nanoparticles, antibacterial, wound bacteria